Recombinant activated factor VII in the management of acute fatty liver of pregnancy: A case report. Issue 7 (21st March 2015) - K, Supriya; Thunga, Suchitra; Narayanan, Athira; Singh, Prakhar
Abstract A 20‐year‐old woman, primigravida at 36+4 weeks' gestation presented with malaise, vomiting for 1 week, yellowish discoloration of the eyes for 3 days and loss of fetal movements. A clinical diagnosis of acute fatty liver with intrauterine fetal demise was made. Labor was induced with prostaglandin E2 gel and delivered vaginally. The post‐partum period was complicated by atonic post‐partum hemorrhage, an episode of seizure, recurrent hypoglycemic attack, hypokalemia and continuing coagulopathy. Supportive management in the intensive care unit using blood and blood products and injection recombinant activated factor VIIa to arrest the bleeding resulted in a successful outcome.